1986
DOI: 10.1002/jcp.1041290210
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of intracellular glutathione content associated with mitogenic stimulation of quiescent fibroblasts

Abstract: The relationship between total glutathione (GSH) content and cell growth was examined in 3T3 fibroblasts. The intracellular GSH level of actively growing cultures gradually decreases as these cells become quiescent by either serum deprivation or high cell density. Upon mitogenic stimulation of sparse, quiescent (G0/G1) cultures with serum, there is a rapid 2.3-fold elevation in intracellular GSH levels which is maximal by 1 h and returns to baseline by 2 h. This is followed by a more gradual increase in GSH co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
82
1
2

Year Published

1989
1989
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(96 citation statements)
references
References 37 publications
11
82
1
2
Order By: Relevance
“…In cell types such as lymphocytes and fibroblasts, an increased GSH level is associated with an early proliferative response and is essential for the cell to enter the S phase (Shaw and Chou, 1986;Messina and Lawrence, 1989;Hamilos et al, 1989;Iwata et al, 1994;Poot et al, 1995). We also reported increased GSH levels during proliferation of rat hepatocytes such as plating primary cultures of rat hepatocytes under low density, which stimulates hepatocytes to shift from G 0 to G 1 phase of the cell cycle (Lu and Ge., 1992), and after 2/3 partial hepatectomy (PH) (Huang et al, 1998).…”
Section: Gsh As a Regulator Of Growth And Deathmentioning
confidence: 99%
“…In cell types such as lymphocytes and fibroblasts, an increased GSH level is associated with an early proliferative response and is essential for the cell to enter the S phase (Shaw and Chou, 1986;Messina and Lawrence, 1989;Hamilos et al, 1989;Iwata et al, 1994;Poot et al, 1995). We also reported increased GSH levels during proliferation of rat hepatocytes such as plating primary cultures of rat hepatocytes under low density, which stimulates hepatocytes to shift from G 0 to G 1 phase of the cell cycle (Lu and Ge., 1992), and after 2/3 partial hepatectomy (PH) (Huang et al, 1998).…”
Section: Gsh As a Regulator Of Growth And Deathmentioning
confidence: 99%
“…It has been reported that elevation of intracellular GSH in tumour cells is associated with mitogenic stimulation (Shaw & Chou, 1986), that GSH controls the onset of tumour-cell proliferation by regulating protein kinase C activity and intracellular pH (Terradez et al, 1993). GPx and GR decrease and protein oxidation increases in patients with glioblastoma multiforme and transitional meningioma and clear different oxidative status was found in the two kinds of tumors which represent specially one of the most malignant and most benign tumors respectively and it was shown that there is a complex relationship between pro-and anti-apoptotic molecules in glioblastoma multiforme pathogenesis, thus targeting multiple pathways with advanced chemotherapeutic agents or radiotheraupetic regimens following total resections might be helpful in patients with glioblastoma multiforme (Atukeren et al, 2010).…”
Section: Antioxidant Status Of the Brainmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Many studies involving lymphocytes and fibroblasts showed that an increased GSH level was associated with an early proliferative response and was essential for the cell to enter the S phase. 2,4,7,8 We showed previously that plating primary cultures of rat hepatocytes under low density, which stimulates hepatocytes to shift from the G 0 to the G 1 phase of the cell cycle, resulted in increased levels of GSH and cysteine, and increased activity of ␥-glutamylcysteine synthetase (GCS), the rate-limiting enzyme in GSH synthesis, as early as 4 hours after plating. 9 The increase in GCS activity was caused by an increase in the GCS-heavy subunit (GCS-HS) gene expression.…”
mentioning
confidence: 99%